A simply prepared small-diameter artificial blood vessel that promotes in situ endothelialization. (May 2017) - Guo, Hong-Feng; Dai, Wei-Wei; Qian, De-Hui; Qin, Zhe-Xue; Lei, Yan; Hou, Xiao-Yu; Wen, Can
Graphical abstract: Abstract: Synthetic grafts are of limited use in small-diameter vessels (Φ < 6 mm) due to the poor patency rate. The inability of such grafts to achieve early endothelialization together with the compliance mismatch between the grafts and the native vessels promote thrombosis, which eventually leads to graft occlusion. In the current study, stromal cell-derived factor (SDF)-1α/vascular endothelial growth factor (VEGF)-loaded polyurethane (PU) conduits were simply prepared via electrospinning. The mechanical property, drug release behavior and cytocompatibility of the conduits were investigated. The effects of the conduits on endothelial progenitor cell (EPC) mobilization and differentiation were examined in vitro. Then, the conduits were implanted as canine femoral artery interposition grafts. The results revealed that SDF-1α and VEGF were quickly released shortly after implantation, and the conduits exhibited slow and sustained release thereafter. The cytokines had definite effects on EPC mobilization and differentiation in vitro and promoted conduit endothelialization in vivo. The conduits had good tissue compatibility and favorable compliance. All of these features inhibited the conduits from being occluded, thereby improving their long-term patency rate. At 6th month postoperatively, 5 of the 8 grafts were patent while all the 8 grafts without the cytokines were occluded. These findings provide a simple and effective method for the construction of small-diameter artificial blood vessels with the aim of facilitating early endothelialization and improving long-term patency. Statement of Significance: (1) SDF-1α/VEGF loaded PU conduits were simply prepared by electrospinning. The cytokines with definite and potent effects on angiogenesis were used to avoid complicated mechanism researches. Compared with most of the current vascular grafts which are of poor strength or elasticity, the conduits have favorable mechanical property. All of these inhibit the conduits from occlusion, and thus improve their long-term patency rate. (2) For the in vivo tests, the dogs did not receive any anticoagulant medication in the follow-up period to expose the grafts to the strictest conditions. In vivo endothelialization of the conduits was thoroughly investigated by Sonography, HE staining, SEM and LSCM. The study will be helpful for the construction of small-diameter artificial blood vessels.